Variation of organic matter quantity and quality in streams at Critical Zone Observatory watersheds. Issue 10 (25th October 2016) - Miller, Matthew P.; Boyer, Elizabeth W.; McKnight, Diane M.; Brown, Michael G.; Gabor, Rachel S.; Hunsaker, Carolyn T.; Iavorivska, Lidiia; Inamdar, Shreeram; Johnson, Dale W.; Kaplan, Louis A.; Lin, Henry; McDowell, William H.; et al.
Abstract: The quantity and chemical composition of dissolved organic matter (DOM) in surface waters influence ecosystem processes and anthropogenic use of freshwater. However, despite the importance of understanding spatial and temporal patterns in DOM, measures of DOM quality are not routinely included as part of large‐scale ecosystem monitoring programs and variations in analytical procedures can introduce artifacts. In this study, we used consistent sampling and analytical methods to meet the objective of defining variability in DOM quantity and quality and other measures of water quality in streamflow issuing from small forested watersheds located within five Critical Zone Observatory sites representing contrasting environmental conditions. Results show distinct separations among sites as a function of water quality constituents. Relationships among rates of atmospheric deposition, water quality conditions, and stream DOM quantity and quality are consistent with the notion that areas with relatively high rates of atmospheric nitrogen and sulfur deposition and high concentrations of divalent cations result in selective transport of DOM derived from microbial sources, including in‐stream microbial phototrophs. We suggest that the critical zone as a whole strongly influences the origin, composition, and fate of DOM in streams. This study highlights the value of consistent DOM characterization methods included as part of long‐term monitoring programs for improving our understanding of interactions among ecosystem processes as controls on DOM biogeochemistry. Key Points: Atmospheric, terrestrial, and aquatic ecosystem forcings interact to control DOM quantity and quality Collection of samples for DOM as part of monitoring programs provides an understanding of processes that influence stream water quality Analysis of DOM across gradients can only be conducted where errors linked to interinstrument comparisons do not play a large role